(untitled) (IAHS Medical Journal, 2022)
Background: Drowning is an important cause of mortality among children in rural Bangladesh. This study was done to find out the sociodemographic characteristics of drowning affected children. Materials and methods : It is a descriptive study among the victim of drowning admitted in the Department of Pediatrics, Chittagong Medical College Hospital, Chattogram during the period of January 2014 to December 2014. One hundred victims were selected for the study. History and face to face interview were taken, the sociodemographic characteristics were analyzed statistically. Results: Of 100 patients in this study, age ranged from 6 month to 12 years, largest number (76%) of victims belonged to 1-4 years age group. Most of the drowning events occurred in rural area (82%). Almost all (87%) of rural drowning occurred in pond, 8% drowning occurred in bucket, all of which were urban. April to October (88%) were found to be high risk months for drowning. Almost all (96%) of the victims were found unable to swim and in 100% cases, there is no fencing present around pond. Most (82%) of the victim survived without morbidity, 6% died, 4% survived with morbidity. Conclusion: Children of 1-4 years old, rural children,children of poor socioeconomic background are vulnerable to drowning. Drowning mostly occurs during daylight, lack of supervision of child is strongly associated with drowning. Drowning has specific seasonal pattern. Busy mother with a large family, illiterate mother, lack of pond fencing or door fencing, and lack of swimming ability are also associated with drowning. IAHS Medical Journal Vol 5(1), June 2022; 38-44